2003
DOI: 10.1103/physrevc.67.045203
|View full text |Cite
|
Sign up to set email alerts
|

φ meson mass and decay width in nuclear matter

Abstract: The φ meson spectrum, which in vacuum is dominated by its coupling to theKK system, is modified in nuclear matter. Following a model based on chiral SU (3) dynamics we calculate the φ meson selfenergy in nuclear matter considering the K andK in-medium properties. For the latter we use the results of previous calculations which account for S− and P −wave kaon-nucleon interactions based on the lowest order meson-baryon chiral effective Lagrangian, and this leads to a dressing of the kaon propagators in the mediu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

13
161
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(176 citation statements)
references
References 31 publications
(87 reference statements)
13
161
2
Order By: Relevance
“…The comparison of the ratios with the work of the Valencia group [2,14,15] results in an about 1.6 times smaller in-medium broadening of the φ compared to the findings using the Paryev model. In between those two models lie the first results from the ongoing Rossendorf Boltzmann-Uehling-Uhlenbeck (BUU) calculations [25].…”
mentioning
confidence: 49%
See 1 more Smart Citation
“…The comparison of the ratios with the work of the Valencia group [2,14,15] results in an about 1.6 times smaller in-medium broadening of the φ compared to the findings using the Paryev model. In between those two models lie the first results from the ongoing Rossendorf Boltzmann-Uehling-Uhlenbeck (BUU) calculations [25].…”
mentioning
confidence: 49%
“…Investigations with elementary (γ,π,p) probes in nuclear collisions, in so-called cold static matter, can cause comparable changes in the properties [1,2,3,4]. Current overviews of this active research field are to be found in Refs.…”
mentioning
confidence: 99%
“…Although originally the ρ meson properties were mostly investigated, nowadays the φ properties have got a lot of interest, because the medium renormalization in this case is more drastic than that of the ρ. Indeed, predictions of an increase of the φ width by a factor five or six [ 2,3] to ten [ 4], at normal nuclear matter density, have been made using different chiral approaches. Different reactions have been studied or suggested to test experimentally this large width [ 5,6,4,7,8,9].…”
mentioning
confidence: 99%
“…[ 3] and its extension to finite φ-meson momentum done in [ 9]. This model is based on the modification of theKK decay channel in the medium by means of a careful treatment of the in medium antikaon selfenergies [ 2].…”
mentioning
confidence: 99%
See 1 more Smart Citation